Case Study of Heterogeneity Index’s Effect on The Successful Workover Based on The Apriori Algorithm - Fahrizal Maulana; Amega Yasutra; Zuher Syihab (Testing Center for Oil and Gas LEMIGAS, 2025)
The Indonesian government has set a target to reduce the consumption-production gap by increasing national oil production to 1 million barrels of oil per day (BOPD) and 12 billion standard cubic feet per day (BSCFD) of gas by 2030. Amongst several approaches, the optimization of mature fields offers a significant opportunity for quick production gains. However, analyzing these fields presents challenges due to the complexity, incompleteness, and poor quality of historical data. Heterogeneity Index (HI) is one of the methods that quickly measure well performance. This method is as simple as measuring a certain well as compared to the average performance at certain time. The parameter being used might vary, but production data is the most frequent one given its availability. Despite simple and practical, skepticism on the reliability of this method is still questionable. This work revisited